Biosorption Tendency of Cichorium intybus for Roccelline NS in Aqueous Solution - Shahid, Samina; Afshan, Gul; A. Qureshi, Fahim; Adnan, Ahmad; Asam Raza, Muhammad; Rehman, Shafiq-ur (Asian Journal of Chemistry, 2011)
The present study was conducted to evaluate the Cichorium intybus as a biosorbent for the removal of roccelline NS from aqueous solution. C. intybus belongs to family Asteraceae is perennial herb and widely distributed through out Pakistan. Roccelline NS is an anionic dye, extensively used in textile industry in Pakistan and its removal from the aqueous solution is a serious problem. Different parameters such as pH, dye concentrations, biosorbent concentrations and particle size of biosorbent were studied on activated and unactivated biosorbent. Langmuir model was used to describe the biosorption phenomenon. It was concluded that activated biosorbent is most active for the removal of dye as compared to the inactivated. FTIR spectra showed that amino group adsorbed the dye thorough the electrostatic attraction between the positive charge of dye and negative charge of biosorbent.